Evaluation Effect of Tenofovir Alafenamide (TAF) in Long-Term Therapy for Chronic Hepatitis B: A Systematic Review - Saputra, Rada Citra; Hidayat, Nur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Tenofovir alafenamide (TAF) is phosphonamidate prodrug of tenofir that inhibits hepatitis B virus and HIV type-1 reverse transcription. TAF more stable form in plasma than tenofovir disoproxil fumarate (TDF) as choice treatment before. TAF in long-term treatment also significantly reduced bone mineral density (BMD) and raised serum creatinine, as well as improved markers of renal tubular function. This study aims to review the long-term therapy of TAF effect in body weight gain, BMD, renal function, lipids profile, ALT normalization, and HBeAg loss.Method: The data was taken from Pubmed, ScienceDirect, and Cochrane Library. We found 363 articles from databases. The articles related to long-term therapy in chronic hepatitis-B and adjusted according to restriction criteria. Articles selection using PRISMA flowchart and quality test using GRADE method into eligible articles.Results: We selected articles that eligible for systematic review with different GRADE recommendation which were 4 high-grade articles, 1 low-grade, and 1 very low-grade article. TAF in long-term therapy showed an increase in BMD (p 0.001), body weight gain (p 0.001), decreased renal dysfunction (CrCl; p 0.0001 and GFR; p = 0.027), and normalized ALT (p = 0.016). However, lipids profile level increase that could increase risk of atherosclerosis and dyslipidemia. There was no significant in HBeAg loss.Conclusion: TAF therapy is favourable therapy in long-term therapy of chronic hepatitis B patients by smaller reduce of BMD, and significant body weight gain, reduce renal dysfunction, good improvement in lipid profile and improving ALT enzymes.